How do Parents allocate Time ? - Hans G. Bloemen; Elena G.F. Stancanelli (Tinbergen Institute, 2008)
This paper focuses on the time allocation of spouses and the impact of economic variables. We present a stylized model of the time allocation of spouses to illustrate the expected impact of wages and non-labour income. The empirical model simultaneously specifies three time-use choices -paid work, childcare, and housework- and wage and employment equations for each spouse, allowing for correlation across the errors of the ten equations. We exploit the rich information in the French time-use survey 1998-99 to estimate the model. The predictions of the theoretical model are mostly validated with the main exception of the standard hypothesis that performing housework does not bring utility. Parents' market time responds positively to changes in own wage. The own-wage elasticity of housework is negative while childcare does not react to changes in own wage. Women's non-market time is independent of their husband's wage; but both housework and childcare of fathers react positively to an increase in their wife's wage. Non-labour income reduces paid work by parents and increases their non-market time. Higher-educated and older parents spend more time with their children. There are significant and positive correlations across the errors of the spousal equations.
Keywords: D1; D13; J21; 330; Time Use; Work Behaviour; Household Economics; Zeitverwendung; Eltern; Kinderbetreuung; Erwerbstätigkeit; Haushaltseinkommen; Frankreich